New Cu-Al Based Quaternary and Quinary High Temperature Shape Memory Alloy Composition Systems - Karaduman, O.; Ozkul, I.; Altin, S.; Altin, E.; Baglayan, O.; Canbay, C. Aksu (Amer Inst Physics, 2018)
The Cu-rich HTSMAs (high temperature shape memory alloys) with new compositions of a quaternary Cu24.07Al- 1.85Ti-1.40Co (at%) and a quinary Cu-24.08Al-2.23Fe-1.34Co-0.97Ti (at%) were fabricated by arc melting and analysed by differential thermal analysis (DTA), X-ray and optical microscopy measurements to find out the thermal and structural properties of the alloys. During thermal measurements, the alloy samples exhibited very well characteristic hysteresis curves of martensitic transformations at high temperatures far above 200 degrees C and their characteristic martensite and austenite phase transition temperatures and kinetic parameters such as enthalpy, entropy and equilibrium temperatures were calculated. The structural X-ray diffraction lattice planes and metallographic semblances on the surface morphology of the crystal natured alloy samples were determined and these results indicated the martensite forms at room temperature. In conclusion, deploying of these new composed alloys in miscellaneous HTSMA applications may be viable.
34th International Physics Congress (IPS) of the Turkish-Physical-Society (TPS) -- SEP 05-09, 2018 -- Konacik, TURKEY
Keywords: Martensitic-Transformation; Microstructure; Phase; Ti